Framing of Sewol ferry tragedy: a comparative analysis of South Korean newspapers - Yang, Lai Fong; Sohee Jeon; Wan Idros Wan Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2016)
On April 16, 2014, a ferry named Sewol was on its way from Incheon to Jeju Island in South Korea, with 476 people on board. Most of the passengers were high school juniors on a school trip. After a sudden turn off at the southeastern coast, the ferry listed and subsequently drifted in the sea for nearly three hours. The ferry captain instructed the passengers to stay in their cabins until a rescue team reached while he and some other crew members abandoned the ship without informing others to escape. Consequently, only 172 people got off the Sewol ferry before it totally capsized and sank. In the months of rescue and search, the remains of 295 passengers and crew members were recovered from the shipwreck at the cost of the lives of two divers. Nine victims are still unaccounted for. This study aims to examine the framing of the Sewol ferry tragedy by three South Korean newspapers, which undertook different political orientations. The findings indicated that the newspapers reported the tragedy with different intensity and prominence, while employing different news sources. Responsibility was found to be the most salient frame in the coverage by the three newspapers. In addition, this study also found that the newspapers were mostly employing neutral valence in reporting the Sewol ferry tragedy.